In optimized rubrene-based nanoparticle blends for photon upconversion, singlet energy collection outcompetes triplet-pair separation, not singlet fission. Issue 12 (19th October 2021) - Bossanyi, David G.; Sasaki, Yoichi; Wang, Shuanqing; Chekulaev, Dimitri; Kimizuka, Nobuo; Yanai, Nobuhiro; Clark, Jenny
Abstract : Conversion of near-infrared photons to visible light in rubrene based systems is made 20x more efficient when mixed with 0.5% wt DBP. This is not because singlet fission in rubrene is supressed, but because of reduced triplet losses. Abstract : The conversion of near-infrared photons to visible light through triplet–triplet annihilation upconversion offers an enticing strategy for significantly boosting the efficiency of conventional solar cell technology. Rubrene is widely employed as the acceptor molecule for realising such upconversion, yet in the solid state, the reverse process of singlet fission is believed to hinder efficient upconversion. Consequently, rubrene is sometimes doped at low concentration (0.5 mol%) with the singlet energy collector tetraphenyldibenzoperiflanthene (DBP) which harvests singlet energy via Förster transfer. Although singlet fission is a multi-step process involving various intermediate triplet-pair states, the interplay between it, triplet recombination and singlet energy collection has not been studied in detail to date. Here we use both transient absorption and time-resolved fluorescence spectroscopy to investigate the dynamics of both singlet and triplet species in rubrene-based nanoparticle films. Strikingly, we find that energy transfer from rubrene to DBP does not outcompete the formation of triplet-pairs through singlet fission, despite the fact that DBP doping increases the photoluminescence quantum yield of the nanoparticle films from 3% to 61%. We rationalise this surprising result in the context of the well-known effects of triplet fusion and triplet-quenching defects on the photoluminescence yield of crystalline rubrene.